PENENTUAN SEKTOR BASIS, KLASIFIKASI SEKTOR DAN ANALISIS SHIFT SHARE DI KABUPATEN KETAPANG - B61109028, YULIUS LAY (Jurnal Ekonomi Daerah (JEDA), 2014)
ABSTRACT Economic growth of region is one of the indicated that can be used to see how the implementation of a regional development of various economic sectors, which directly describe the rate of economic growth. Changes in governance systems provide a significant influence in the management of regional development. Patterns of regional development and planning system which previously tended top down has turned into more varied depend on the potential and the fundamental problems faced in the region. This condition push competition among regions to promote economic growth and welfare. As a consequence of the limited resources, the implementation of development should be focused on the development sectors that give multiplier effect greatly to other sectors or the economy as whole. This study aims to determine the basic sector, sector classification and shift share analysis in Ketapang as information and considerations in planning economic development. This study uses secondary data by the time series of Gross Regional Domestic Product Ketapang District and West Kalimantan Province in 2007 2011. The tools used in research is Klassen Tipology Analysis, Location Quotient (LQ) Analysis and Shift Share Analysis. The result of Klassen Tipology Analysis indicate the sector which can growing rapidly advanced are the agricultural sectors, mining sectors and processing industry sectors. Location Quotient Analysis show agricultural sector, mining sector, and the sector of processing industry is a basic sector in the Ketapang District. Shift Share Analysis indicate that the competitive are processing industry sektor, power, gas and water supply sector and trade, hotel and restaurant sector. The result on the basic sector, based on the three tools of analysis shows that the sector as a basic sector, with criteria belong to the advanced sector and rapidly growing and competitive is the processing industry sector, in particular sub-sectors of food processing, beverages and tobacco. This sub-sector is potential sub-sector to be developed as the leading sector in Ketapang Distric. Keyword: Basic Sector, Klassen Tipology, Location Quotient and Shift Share.